Expressive writing for wildfire-affected pregnant women: Themes of challenge and resilience. (November 2020) - Brémault-Phillips, Suzette; Pike, Ashley; Olson, Joanne; Severson, Emily; Olson, David
Abstract: The worst disaster of natural origin in recent Canadian history occurred in May 2016 in the northern Alberta community of Fort McMurray Wood Buffalo (FMWB). Among the 88, 000 people abruptly evacuated amidst a raging wildfire were approximately 1850 pregnant or pre-conception women. Based on the Allostatic Load and Preterm Birth Conceptual Framework (Olson et al., 2015) [1], a simple, cost-effective expressive writing intervention following Pennebaker's work (Pennebaker and Beall, 1986; Pennebaker et al., 2007) [2, 3] was implemented in a primary study to help mitigate the negative effects of stress on a sample of these women and their unborn children. Journal writing served as an intervention in the primary study while the contents of the journal entries became the data analyzed in this qualitative study. This study utilized both inductive and deductive thematic analysis of journal entries completed by 54 women over four consecutive days (15 min/day). Deductive analysis followed a coding structure that was generated from two resilience scales. Themes that emerged during inductive analysis were also coded. The main themes that emerged described the women's challenging experiences: fears for themselves and their offspring, fire-related and past trauma, and relationship changes. Resilience characteristics and practices also emerged from the writings and mirrored those found in the literature: (a) post-traumatic growth, (b) adaptability, (c) emotional/social connectedness, (d) composure, and (e) reasoning. This paper highlights the challenging experiences of pregnant women exposed to a disaster and the resilience they demonstrated in the face of the tragedy.